DYNAMIC GEOMETRY ENVIRONMENTS AS COGNITIVE TOOL IN MATHEMATIC EDUCATION - POLÁŠEK, Vladimír; SEDLÁČEK, Lubomír (Journal of Technology and Information Education, 2015)
In this paper we deal with a possibility of the application of dynamic and interactive geometry software in the mathematics teaching at our schools. We offer their brief characteristics and describe their integration among cognitive computing technologies. The greater attention is paid to GeoGebra Software in order to show its specific use as a cognitive tool. We describe the importance and the role of dynamic geometry programs in the discovery of new knowledge by the experimentation and manipulation of the interactive construction. Each phase of this process we generally define and then illustrate with a specific example.
Keywords: cognitive technology; dynamic and interactive geometry; GeoGebra; experiment; hypothesis; verification; proof